2014
DOI: 10.1159/000369343
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Muscular Dystrophies: A Systematic Literature Review

Abstract: Background: Determiningtheprevalence of neuromuscular disorders for the general population is important to identify the scope of burden on society and enable comparisons with other health conditions. This systematic review aims to identify and collate the findings of studies published between 1960 and 2013 on the prevalence of all types of muscular dystrophies. Summary: Relevant articles were identified through electronic database searches and manual searches of reference lists. There were 38 articles from acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
150
1
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 1,433 publications
(180 citation statements)
references
References 55 publications
3
150
1
12
Order By: Relevance
“…This represents a lack of effort to make data from populations with different demographic structure comparable. Indeed, in a recent systematic literature review on the prevalence of muscular dystrophies worldwide, Theadom and colleagues identified only one study reporting age-standardized prevalence and no studies presenting age or gender distribution [26] .…”
Section: Discussionmentioning
confidence: 99%
“…This represents a lack of effort to make data from populations with different demographic structure comparable. Indeed, in a recent systematic literature review on the prevalence of muscular dystrophies worldwide, Theadom and colleagues identified only one study reporting age-standardized prevalence and no studies presenting age or gender distribution [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, whilst standardized methods of reporting have become widespread with other common conditions, such as stroke, there remains a lack of consistency in conditions such as MD. This may be reflected in the considerable variability found in current reported prevalence between 0.5 and 18.1 per 100,000 [2] .…”
mentioning
confidence: 93%
“…A recent study exploring prevalence of all neuromuscular disorders in the Republic of Ireland [6] utilised a community patient support service to assist in identifying cases; however, the study only included those aged 18 years or over. Previous epidemiological studies of genetic muscle disorders are consequently prone to selection and diagnostic biases [7]. This nationwide population-based study aimed to explore prevalence of genetic muscle disorders in New Zealand (NZ) by age, sex, ethnicity, region and disorder type.…”
Section: Introductionmentioning
confidence: 99%